Implementasi Teori Social Learning Albert Bandura dalam Pembentukan Karakter Islami Anak Usia Dini Di Era Digital 2026 - Shofia Hikmatuzzohrah; Mahsur; Hizbul Wathoni (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to conduct an in-depth analysis of the implementation of Albert Bandura’s Social Learning Theory in shaping Islamic character among early childhood learners in the digital era of 2026. The research employs a qualitative approach with a case study design at a technology-integrated Islamic Early Childhood Education institution. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis utilized the interactive model of Miles and Huberman, and validity was strengthened through source and method triangulation. The findings indicate that teacher and parent modeling serves as the dominant factor in the internalization of Islamic values such as honesty, discipline, responsibility, empathy, and social etiquette. The implementation of Social Learning Theory becomes effective when accompanied by positive reinforcement, structured worship habituation, Islamic digital literacy, and strong collaboration between school and family. The digital era presents challenges in the form of symbolic modeling through digital media, which can influence children's imitative behavior. This study proposes an implementative Social Learning model grounded in Islamic values that is contextualized to the challenges faced by Generation Alpha. The research confirms that the integration of modeling, Islamic digital literacy, and school–family collaboration constitutes the primary strategy in fostering Islamic character development among early childhood learners in the digital era